2017
DOI: 10.1093/mnras/stx2238
|View full text |Cite
|
Sign up to set email alerts
|

Subhalo demographics in the Illustris simulation: effects of baryons and halo-to-halo variation

Abstract: We study the abundance of subhaloes in the hydrodynamical cosmological simulation Illustris, which includes both baryons and dark matter in a ΛCDM volume 106.5 Mpc a side. We compare Illustris to its dark matter-only (DMO) analog, Illustris-Dark, and quantify the effects of baryonic processes on the demographics of subhaloes in the host mass range 10 11 to 3 × 10 14 M . We focus on both the evolved (z = 0) subhalo cumulative mass functions (SHMF) and the statistics of subhaloes ever accreted, i.e. infall subha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 85 publications
7
66
0
Order By: Relevance
“…To 9 This threshold is not fully equivalent to M z = 0 tot > 5 × 10 8 M in the DMonly (DMO) version, because the DM particles in the DMO simulations also account for the mass contributed by baryons and are therefore more massive, by a factor of (1 − Ω b /Ω m ) −1 = 1.19. 10 Note that the absolute survival fractions in the DM-only simulation of Chua et al (2017) are significantly higher than in our Fig. 4, because they do not explicitly include the pre-processing phase.…”
Section: Thresholds In Total Galaxy Massmentioning
confidence: 71%
See 3 more Smart Citations
“…To 9 This threshold is not fully equivalent to M z = 0 tot > 5 × 10 8 M in the DMonly (DMO) version, because the DM particles in the DMO simulations also account for the mass contributed by baryons and are therefore more massive, by a factor of (1 − Ω b /Ω m ) −1 = 1.19. 10 Note that the absolute survival fractions in the DM-only simulation of Chua et al (2017) are significantly higher than in our Fig. 4, because they do not explicitly include the pre-processing phase.…”
Section: Thresholds In Total Galaxy Massmentioning
confidence: 71%
“…The small net influence of baryons is also is at odds with the recent study of Chua et al (2017), who found that, in the Illustris simulation, the inclusion of baryons reduces the survival fraction by ≈ 5-20 per cent, at all masses. It is plausible that these differences reflect different sub-grid physics implementations, so that a destabilizing effect of gas stripping dominates in Illustris, while it is approximately cancelled by the cohesive effect of star formation in Hydrangea 10 .…”
Section: Survival Fractions Of Satellitesmentioning
confidence: 74%
See 2 more Smart Citations
“…Limousin et al 2009, Munari et al 2016, 2017. Such a comparison can shed light on baryionic processes shaping cluster substructure, dynamical processes leading to halo stripping in different environments, and indirectly on the nature of dark matter (Despali & Vegetti 2017;Chua et al 2017;Nipoti et al 2018;Niemiec et al 2019).…”
Section: Introductionmentioning
confidence: 99%